Analyzing the Students’ Interest on the Use of Semantic Mapping Strategy in Improving Students Writing Skill - Opik Dwi Indah; Juwita Crestiani (Institut Agama Islam Negeri Palopo, 2021)
This research used descriptive quantitative method. It aimed at finding out and analyzing students’ interest on the use of mind mapping strategy to improve the students writing skill. To gain the data, the researchers used questionnaire with 10 statements. The researchers took second grade students of SMP Satap Pongsamelung and chose 10 students as participants. The data shows that they have good response towards the use of semantic mapping strategy such as: they were always interested, felt helpful and happy to learn English using this strategy particularly in improving their writing skill. Based on the result of this research, it can be concluded that that most of the students were interested to improve their writing skill using semantic mapping strategy.